2013
DOI: 10.2119/molmed.2012.00343
|View full text |Cite
|
Sign up to set email alerts
|

Replacement of the C6ORF66 Assembly Factor (NDUFAF4) Restores Complex I Activity in Patient Cells

Abstract: Disorders of the oxidative phosphorylation (OXPHOS) system frequently result in a severe multisystem disease with the consequence of early childhood death. Among these disorders, isolated complex I deficiency is the most frequently diagnosed, accounting for one-third of all cases of respiratory chain deficiency. We chose to focus on complex I deficiency, caused by mutation in the assembly factor chromosome 6, open reading frame 66 (C6ORF66; NADH dehydrogenase [ubiquinone] complex I assembly factor 4 [NDUFAF4]… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
0
16
0
1
Order By: Relevance
“…The consequences of NDUFAF4 variants for CI assembly in patient fibroblasts have previously not been studied. 2,6,11 Our recently published detailed human CI assembly model has shown that the CI assembly process mirrors its modular architecture: 1 subunits of the different functional modules are assembled separately and most intermodular association does not take place until the final steps of CI biogenesis. NDUFAF4 is associated with assembly intermediates of the Q-module.…”
Section: Discussionmentioning
confidence: 99%
“…The consequences of NDUFAF4 variants for CI assembly in patient fibroblasts have previously not been studied. 2,6,11 Our recently published detailed human CI assembly model has shown that the CI assembly process mirrors its modular architecture: 1 subunits of the different functional modules are assembled separately and most intermodular association does not take place until the final steps of CI biogenesis. NDUFAF4 is associated with assembly intermediates of the Q-module.…”
Section: Discussionmentioning
confidence: 99%
“…In the past decade, several groups have been successful in this endeavor. A group out of Hebrew University–Hadassah Medical School, led by Hala Lorberboum-Galski, has developed and successfully delivered functional proteins to the mitochondria in vitro to restore defects in the electron transport chain (51) and acetyl Co-A production (52) associated with life-threatening mitochondrial disease. Other groups have also demonstrated the ability to deliver functional copies of proteins into cells to alleviate dysfunctional proteins associated with mitochondrial and lysosomal diseases.…”
Section: Busting Out: Escape From the Endosomementioning
confidence: 99%
“…While TAT–Ndi1 was introduced into Langendorff‐perfused rat hearts, this fusion protein was not only localized to mitochondria but also significantly ameliorated reperfusion injury. In 2013, Marcus et al . applied the TAT system to deliever the protein NADH dehydrogenase (ubiquinone) complex I, assembly factor 4 (NDUFAF4; or C6orf66) into patient cells and their mitochondria, leading to the proper assembly and function of complex I.…”
Section: Tat‐mediated Protein Transduction For Complex I Deficiencymentioning
confidence: 99%